Hakikat Pendekatan dan Metode Dalam Pembelajaran Bahasa - Bidin, S.Ag., M.Pd. (STAI Kuala Kapuas, 2023)
So far, there has been an impression of mixing understanding between approaches, methods, and techniques in learning. In the lesson plan, it is often said that lectures, discussions, assignments, and questions and answers are a method. While others refer to learning techniques. Some say